2015
DOI: 10.1186/s13104-015-1576-z
|View full text |Cite
|
Sign up to set email alerts
|

A prospective pilot study of detection of sentinel lymph nodes in gynaecological cancers using a novel near infrared fluorescence imaging system

Abstract: BackgroundSentinel Lymph Node (SLN) sampling may significantly reduce surgical morbidity by avoiding needless radical lymphadenectomy. In gynaecological cancers, the current practice in the UK is testing the accuracy of SLN detection using radioactive isotopes within the context of clinical trials. However, radioactive tracers pose significant logistic problems. We, therefore, conducted a pilot, observational study to assess the feasibility of a novel optical imaging device for SLN detection in gynaecological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 30 publications
(36 reference statements)
0
26
0
Order By: Relevance
“…However, if the resected lymph nodes were not involved, which is often the case in early stage cervical cancer, patients underwent unnecessarily lymphadenectomy. This could be prevented by performing SLN mapping, for instance with NIR fluorescence imaging, as shown in different studies . These studies, performed in early stage cervical cancer, showed detection rates varying from 60% to 100%.…”
Section: Sentinel Lymph Node Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if the resected lymph nodes were not involved, which is often the case in early stage cervical cancer, patients underwent unnecessarily lymphadenectomy. This could be prevented by performing SLN mapping, for instance with NIR fluorescence imaging, as shown in different studies . These studies, performed in early stage cervical cancer, showed detection rates varying from 60% to 100%.…”
Section: Sentinel Lymph Node Mappingmentioning
confidence: 99%
“…However, in some centers fluorescence imaging is used for SLN mapping and incorporated in standard care . Nineteen studies showed that fluorescence imaging is useful, indicating high detection rates of lymph nodes, varying from 68 to 100% . Laios et al showed the lowest detection rate (68%), which was probably caused by the learning process as visualized by a learning curve.…”
Section: Sentinel Lymph Node Mappingmentioning
confidence: 99%
“…All of the authors (and many not mentioned here) agree that ICG offers the highest detection rates comparable to those of the standard 99m Tcblue technique but with superior bilaterality [11,26]. ICG achieves greater diffusion; better visualisation; greater bilateral detection, which translates into a lower risk of lymphadenectomy (61% with MB vs. 39% with ICG; p < 0.001 [63]); a shorter surgical time and long-term financial savings and can obviate the need for an injection of radiotracer [68]. It was initially stated that ICG represented an increase in the number of resected SLNs, a finding that became standard with experience in the technique [69].…”
Section: Indocyanine Greenmentioning
confidence: 50%
“…The use of fluorescence in the near infrared (NIR) spectral region has shown that penetration depths of the order of 10s of mm can be achieved [7], at the expense of poorer spatial resolution. More importantly, autofluorescence is significantly reduced [8].…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence-guided surgery (FGS) in the NIR has been successfully performed in a number of laparoscopic procedures including sentinel lymph node (SLN) detection [7,11,12], cholangiography [13], ureter imaging [14] and nerve identification [15] amongst others. These advances have been driven by the availability of fluorescent dyes that are approved for clinical use in off-label studies (i.e.…”
Section: Introductionmentioning
confidence: 99%